PELAKSANAAN PERJANJIAN KERJASAMA PENJUALAN TIKET PENUMPANG KAPAL PT. PELNI (PERSERO) : STUDI DI PT. WAMENGKOLI JAYA BAUBAU - Wa Ode, Zamrud; La Ode Muhammad, Muskur; Taibu, Rachmat; Asmalila, Nida (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
This study aims to determine the implementation of a cooperation agreement for the sale of ship passenger tickets between PT Pelni (Persero) and PT Deputy Mengkoli Jaya and to find out the settlement efforts when one party breaks the promise. The primary data sources come from interviews with sources and observations, and the secondary data sources come from the Civil Code (KUHPer) Law No. 17 of 2008 on Shipping, Marketing of Ship Passenger Tickets Agreement Letter No. TH.02.01.83 / SPK: TH.02.01.83/SS/2021, books, literature and internet articles, and the results of previous research related to the aspects studied. The data will be collected through interviews, observation and literature review. The data obtained is in the form of narrative text, which is a systematic sequence. The results of this study conclude that the cooperation agreement for the sale of ship passenger tickets between PT Pelni (Persero) and PT Wamengkoli Jaya is a standard agreement or written contract in the marketing of ship passenger tickets, which contains rights and obligations, as well as settlement efforts in the event of default by providing administrative sanctions, compensation and disciplinary sanctions.